Pelatihan pembuatan pestisida nabati pada Komunitas Unsulbar Farming Club di Green House Universitas Sulawesi Barat - Ilham, Ilham; Kasim, Niken Nur; Yanti, Nur Aida; Sukmawati, Sri; Arifin, Asia; Sulastri, Elsa; Annisaa, Nurul Wirid (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
This activity was motivated by the relatively low level of understanding and practical skills among farmers and community members in producing and utilizing botanical pesticides in agricultural practices. The primary objective of the training was to equip participants, particularly students affiliated with the Unsulbar Farming Club (UFC), with relevant knowledge and competencies. The training was conducted at the Greenhouse of the Faculty of Agriculture and Forestry, University of West Sulawesi. The training employed a demonstration-based method, which involved direct practical engagement and oral explanations at each stage of the botanical pesticide production process. The main ingredients used during the training included papaya leaves, neem leaves, and distilled water (aqua distillate). A total of 60 student participants attended the training, demonstrating a high level of enthusiasm and active engagement throughout the material delivery and practical demonstrations. The overall activity successfully enhanced participants’ awareness and technical skills related to the preparation and application of botanical pesticides. This outcome was reflected in the assessment results, where 93% of participants (56 out of 60) achieved scores ranging from 65 to 85, corresponding to performance levels from Good (B-) to Excellent (A). Meanwhile, 6.67% of participants (4 individuals) received scores categorized as C and D.